Caracterización de las conductas agresivas en un paciente con TDAH en la Parroquia Barreiro de la ciudad Babahoyo Provincia Los Ríos - Gavidia Marquez, Sandra Zalea (2020)
The present research case was carried out with the purpose of collecting as much information as possible about the attention deficit with hyperactivity, in the Barreiro Parish of the city of Babahoyo De Los Ríos Province, that this alteration constitutes one of the 4 syndromes that are included as basic brain function, and that has been recognized in the last of the descriptions of the Diagnostic and Statistical Manual of Mental Disorders (DSM V). It is described as attention deficit, hyperactivity, low level of frustration, impulsivity and emotional disability. And although there is no suspicion about its organic naturalness, this does not imply an evident mental damage and even less an irreparable brain damage, but a disturbance or a dysfunction of the main brain faculties in the area of behavior. HAVD can be associated with language disorders, learning disorders and motor clumsiness problems. Its diagnosis should be made based on a regular clinical neurological study and neuropsychological assessments. Neuroimaging tests or neurophysiological studies are only recommended when other abnormalities must be eliminated.